Hematopoietic and mesenchymal stem cells: a promising new therapy for spondyloarthritis?. (September 2017) - Rodriguez, Valeria Rios; Llop, Maria; Poddubnyy, Denis
In the last years, a considerable progress has been made in the treatment of spondyloarthritides. Nonetheless, there remain a considerable number of patients who are unresponsive to all current therapies. Since the late 1990s, numerous trials have investigated the use of stem cell transplantation as a new approach for the treatment of autoimmune disease, particularly with hematopoietic stem cell transplantation. More recently, the research has focused on mesenchymal stem cell application due to their low immunogenicity and immunomodulatory properties. In this article, we summarize available data on hematopoietic stem cell and mesenchymal stem cell use for the treatment of spondyloarthritides and discuss the data gaps and possible research agenda in this area.